An Analysis of the Role of Assent in Commitment Bequest - Ã˜ÂºÃ™Â„Ã˜Â§Ã™Â…Ã›ÂŒ, Ã™Â…Ã™Â„Ã›ÂŒÃ˜ÂÃ™Â‡; Ã˜Â³Ã™Â„Ã˜Â·Ã˜Â§Ã™Â†Ã›ÂŒ, Ã˜Â¹Ã˜Â¨Ã˜Â§Ã˜Â³Ã˜Â¹Ã™Â„Ã›ÂŒ; Ã™Â†Ã˜Â§Ã˜ÂµÃ˜Â±Ã›ÂŒ Ã™Â…Ã™Â‚Ã˜Â¯Ã™Â…, Ã˜ÂÃ˜Â³Ã›ÂŒÃ™Â† (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
One of the challenges of civil jurisprudence is the nature of executorship of the will (commitment bequest = waá¹£iyyat âahdiyya) and the issue of assent (qabÅ«l) in it. The renowned majority of ImÄmÄ« jurists believe that assent is not a precondition in commitment bequest. Article 834 of civil law has also approved this view. Although in agreement with the renowned majority of ImÄmÄ« jurists, this article contradicts a number of indisputable legal and judicial rules such as the principle of sovereignty and free will, necessity of assent in contracts, denial of loss, and distress and constriction. On the other hand, it is also impossible to ignore the bequeatherâs (muwassÄ«) offer (Ä«jÄb) since the bequest would be left undecided and bring loss to him/her. Besides the generally accepted view, there are other views in this issue, including that after the death of the bequeather, if the executor (wasyy) has not accepted the execution of the will, he is entitled to reject or when the son is the executor of the father or if the execution of the will (wiá¹£Äya) is not possible by anyone else except the executor himself, he should accept the execution of the will. After refutation and confirmation of the viewpoints, this writing would accept âAllÄma á¸¤illÄ«âs view with a slight difference as follows: the bequeather is legally and lawfully obliged to inform the executor of his object of bequest and to secure his assent before his (the bequeatherâs) death; in this case, no injustice is done neither to the bequeather nor the executor and the contradiction of the two principles of âno harmâ would be eliminated.